TMT-Based Quantitative Proteomics Analysis of Synovial Fluid-Derived Exosomes in Inflammatory Arthritis - Huang, Yukai; Liu, Yuqi; Huang, Qidang; Sun, Shanmiao; Ji, Zhuyi; Huang, Lixin; Li, Zhi; Huang, Xuechan; Deng, Weiming; Li, Tianwang (Frontiers in Immunology, 2022)
Objectives: To compare the proteomics of synovial fluid (SF)-derived exosomes in rheumatoid arthritis (RA), axial spondyloarthritis (axSpA), gout, and osteoarthritis (OA) patients. Methods: Exosomes were separated from SF by the Exoquick kit combined ultracentrifugation method. Tandem mass tags (TMT) labeled liquid chromatography mass spectrometry (LC-MS/MS) technology was used to analyze the proteomics of SF-derived exosomes. Volcano plot, hierarchical cluster, gene ontologies (GO), kyoto encyclopedia of genes and genomes (KEGG) pathway analysis were conducted. Results: A total of 1678 credible proteins were detected. Sixty-nine differentially expressed proteins were found in gout, compared with OA, axSpA, and RA simultaneously. Twenty-five proteins were found highly expressed in gout uniquely, lysozyme C and protein S100-A9 included, whose bioinformatic analysis was significantly involved in “neutrophil degranulation” and “prion diseases”. Eighty-four differentially expressed proteins were found in axSpA, compared with OA, gout, and RA simultaneously. Thirty-nine proteins were found highly expressed in axSpA uniquely, RNA-binding protein 8A and protein transport protein Sec24C included, whose bioinformatic analysis was significantly involved in “acute-phase response” and “citrate cycle”. One hundred and eighty four differentially expressed proteins were found in RA, compared with OA, gout, and axSpA simultaneously. Twenty-eight proteins were found highly expressed in RA uniquely, pregnancy zone protein (PZP) and stromelysin-1 included, whose bioinformatic analysis was significantly involved in “serine-type endopeptidase inhibitor activity” and “complement and coagulation cascades”. Enzyme linked immunosorbent assay (ELISA) result showed that the exosomes-derived PZP level of SF in RA was higher than OA (P＜0.05). Conclusion: Our study for the first time described the protein profiles of SF-derived exosomes in RA, axSpA, gout, and OA patients. Some potential biomarkers and hypothetical molecular mechanisms were proposesed, which may provide helpful diagnostic and therapeutic insights for inflammatory arthritis (IA).